Balloon Sacroplasty as a Palliative Pain Treatment in Patients with Metastasis-Induced Bone Destruction and Pathological Fractures - Andresen, R.; Radmer, S.; Lüdtke, C. W.; Kamusella, P.; Wissgott, C.; Schober, H. C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: In the case of metastatic involvement of the sacrum with destruction and consecutive pathological fracture, intense disabling pain is one of the defining factors. The feasibility, safety and pain development with cement augmentation were to be investigated.Materials and Methods: CT-guided balloon sacroplasty was conducted in 10 patients with metastasis-induced bone destruction of the sacrum. After establishment of the entry point, a K-wire was first introduced as far as the central tumor lesion via the short, or transiliac axis. A cannula was then positioned over the wire. Under CT guidance, a balloon catheter was introduced through the cannula and inflated and deflated several times. The PMMA cement was then injected into the preformed cavity. The procedure was completed by a spiral CT control using the thin-slice technique. Pain intensity was determined using a visual analog scale (VAS) before the procedure, on the 2nd postoperative day and 6 months after the intervention. Finally, the patients were asked to state how satisfied they were.Results: Balloon sacroplasty was technically feasible in all patients. The control CT scan showed central distribution of the cement in the tumor lesion. On average 6 +/– 1.78 (4 – 10) ml of PMMA cement were introduced per treated lesion. A significant (p < 0.001) reduction in pain according to the VAS occurred in all patients from 9.3 +/– 0.67 (8 – 10) pre-operatively to 2.7 +/– 1.28 (1 – 5) on the 2nd postoperative day and 2.9 +/– 0.81 (2 – 5) 6 months after the intervention. All of the patients were re-mobilized after the procedure and underwent the further therapeutic measures as planned.Conclusion: Balloon sacroplasty is a helpful therapeutic option in the overall palliative treatment of patients with tumor-induced destruction. It is a safe and practicable procedure that markedly reduces disabling pain.Key points:• Balloon sacroplaty is a safe method of cement augmentation for osseous destruction• With balloon sacroplasty debilitating lower back pain can be significantly reduced• Balloon sacroplasty is a helpful supplement in palliative therapyCitation Format:• Andresen R, Radmer S, Lüdtke CW et al. Balloon Sacroplasty as a Palliative Pain Treatment in Patients with Metastasis-Induced Bone Destruction and Pathological Fractures. Fortschr Röntgenstr 2014; 186: 881 – 886
Keywords: balloon sacroplasty; metastasis-induced bone destruction; interventional pain therapy; palliative therapy; os sacrum